Simulations and Virtual Laboratories, didactic resource in the teaching of University Mathematics: systematic review. - Cenas Chacón, Fernando Ysmael; Blaz Fernández, Fanny Evelyn; Gamboa Ferrer, Leydidiana Rosibel; Ramírez Sobalvarro, Yasmina (LACCEI, 2025)
Mathematics is considered one of the fundamental disciplines in university education, since it contributes to the formation of skills, a situation that is favored by the use of simulations and virtual laboratories in learning. The objective of this study was to identify the opportunities generated by the use of virtual laboratories and simulation in the learning of mathematics in a period of time from 2019 to January 2024. It was different databases were consulted to carry out the systematic review among these ERIC (Educational Resources Information Center), Google Scholar, Scopus, Redalyc and Dialnet; making use of search formulas (AND, OR), obtaining 274 studies, which were subjected to inclusion and exclusion criteria, and a total of 30 articles were compiled using PRISMA. It was found that the studies analyzed showed that the use of simulation and virtual laboratories are valuable opportunities that contribute to the improvement of students’ academic performance, the acquisition and strengthening of innovative skills, support the organization of learning in a sequential manner and increase the levels of understanding and application of concepts. The multiple studies developed revealed that the use of this type of resources used in educational experiences generated significant learning of mathematics, which in turn allowed students to feel more confident and motivated to solve problematic situations in complex environments.